The macro- and micro-adaptations in the football teams - Fabian Alberto Romero Clavijo; Renata Alvares Denardi; Umberto Cesar Corrêa (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This study investigated the adaptations of football teams as hierarchically organised open systems. In this type of system, the collective and individual behaviours are characterised by consistency and variability, respectively. Methods: Five professional men's football matches in the under-20 category were analysed. The team's centroid as a measure of the system's macrostructure and the distance from each player to the team's centroid (a measure of the system's microstructure) were obtained from the players' x and y coordinates of displacement on the soccer field. Cluster analyses were run using Ward's minimum variance method with Euclidean distance. Results: (i) teams showed consistency and variability in their macro- and microstructures, respectively; (ii) there was a correlation between attack and defence patterns in most game sequences; (iii) goals were scored when teams modified their macro and/or microstructure. Conclusion: Football teams showed correspondence in attack-defense patterns with macro-consistency and micro-variability throughout the match. Despite this, there was no relationship between the foregoing patterns and game outcomes. Goals were scored after changes in the team's structure.